Auditoría de cumplimiento al área de talento humano de la Importadora Adrián Imceal Cía. Ltda., del cantón La Maná, provincia de Cotopaxi, período 2022. - Flores Cedeño, Diana Salome (2024)
The theme of this research project was the Compliance Audit of the Human Resources Area at the Importadora Adrián Imceal Cía. Ltda. La Maná Cantón, Cotopaxi Province, period 2022 with the purpose of analyzing the compliance of the hiring processes carried out by the entity, so guaranteeing the validity of the internal regulations of the company and the external ones according to the competent entities. In order to obtain data, a series of methodologies were used to analyze the results efficiently, such as documentary and descriptive research. On the other hand, the field research allowed collecting data through interviews and surveys applied to the personnel to identify the elements that influence the selection of candidates. The audit determined as a relevant aspect the lack of knowledge about the existence of internal regulations by employees, as well as the fact that there is not previously established process for the selection and hiring of employees. It resulted in the lack of a procedures manual in the Human Resources area which led to propose a "Procedures Manual to improve the management of the Human Resources Area at Importadora Adrián Imceal Cía. Ltda." that aims to establish how to manage the resources in the Human Resources area to obtain better performance, develop the collective welfare of the institution, and build a pleasant working environment.